Answer :



Using the splitting middle term - the middle term of the general equation is divided in two such values that:


Product = a.c


For the given equation a = 3; b = 11 ;c = -4


= 3. - 4 = - 12


And either of their sum or difference = b


= 11


Thus the two terms are 12 and - 1


Difference = 12 - 1 = 11


Product = 12. - 1 = - 12




3x(x + 4)-1(x + 4) = 0


(x + 4)(3x-1) = 0


(x + 4) = 0 or (3x-1) = 0


x = -4 or x = 1/3


Roots of equation are - 4, 1/3


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Which of the follRS Aggarwal - Mathematics

Which of the follRS Aggarwal - Mathematics

Which of the follRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics